2006
DOI: 10.1038/modpathol.3800546
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral lymphatic invasion is associated with regional lymph node metastases in prostate adenocarcinoma

Abstract: Lymphangiogenesis, detected by antibodies specific for lymphatic endothelial cells, has been associated with regional lymph node metastases and poor prognosis in carcinomas of head and neck, breast and uterine cervix, but remains largely uninvestigated in prostate adenocarcinoma. We evaluated the lymphatic vessel density and lymphatic vessel invasion by prostate cancer cells in the intratumoral, peritumoral and normal prostate tissue compartments in cancer-bearing prostate glands and correlated them with lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
76
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 27 publications
9
76
1
3
Order By: Relevance
“…Some studies suggest that lymph vessel density inside intratumoral compartment of prostatic carcinoma is reduced [22,23] as it is in our study. Roma et al [22] associated higher peritumoral lymphatic vessel density with higher Gleason score and peritumoral invasion with frequent lymph node metastasis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Some studies suggest that lymph vessel density inside intratumoral compartment of prostatic carcinoma is reduced [22,23] as it is in our study. Roma et al [22] associated higher peritumoral lymphatic vessel density with higher Gleason score and peritumoral invasion with frequent lymph node metastasis.…”
Section: Discussionsupporting
confidence: 77%
“…Some studies suggest that lymph vessel density inside intratumoral compartment of prostatic carcinoma is reduced [22,23] as it is in our study. Roma et al [22] associated higher peritumoral lymphatic vessel density with higher Gleason score and peritumoral invasion with frequent lymph node metastasis. Cheng et al [23] did not correlate these findings and concluded that quantification of lymphangiogenesis in prostate adenocarcinoma does not offer useful prognostic information.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies have shown that peritumoral lymphatic vessels are associated with lymph node metastasis, 8,14,17,18,27,40,41 whereas other studies, only for head and neck squamous cell carcinoma, showed that intratumoral lymphatic vessels, and not peritumoral lymphatic vessel density, are important for lymphatic spreads. 3,14,15 Thus, we first examined the VEGF-C and D2-40 expression in cholangiocarcinoma S Aishima et al intratumoral or peritumoral lymphatic vessel density in intrahepatic cholangiocarcinomas, and detected the following: (1) lymphatic vessel density was much lower in the tumor center than in the tumor periphery; (2) lymphatic vessels in the tumor center were frequently collapsed, whereas peritumoral lymphatic vessels showed open lumen; and (3) lower lymphatic vessel density in the tumor center was significantly correlated with the presence of lymphatic invasion.…”
Section: Discussionmentioning
confidence: 99%
“…11,44 It was demonstrated that increased lymphangiogenic activity is not required for the lymphatic spread in pancreatic ductal adenocarcinoma, 7,9 and prostatic adenocarcinoma. 8,22 Several studies showed that increased lymphatic perimeters and areas were found to be correlated with presence of lymphatic metastasis. 17,39,40,42 Therefore, lymphatic invasion in intrahepatic cholangiocarcinoma is independent of the active lymphangiogenesis, but other possible factors are expected for the lymphatic spread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation